Erudite Cultural Mediators and the Making of the Renaissance Polymath: The Case of Giorgio Fondulo and Janello Torriani - Zanetti, Cristiano (Renaissance and Reformation / Renaissance et Réforme, 2016)
Janello Torriani, also known by his Spanish name Juanelo Turriano (Cremona ca. 1500–Toledo 1585), was a blacksmith, locksmith, constructor of scientific instruments, famous inventor of mechanical devices, automata-maker, clockmaker to Emperor Charles V, hydraulic engineer, mathematician, star-gazer, bell-designer, surveyor, and author of mathematical treatises to King Philip II of Spain. He was especially famous for his amazing planetary clocks, which he both designed and physically crafted (thanks to the invention of the first known machine-tool to cut gears), and for his hydraulic device of Toledo, the first giant machine in history that elevated water over a slope of ninety metres a distance of three hundred meters. Given this multifaceted professional profile, Torriani has been considered a Renaissance polymath and a genius. This article goes beyond the anachronistic understanding of these two categories, which it deconstructs, by analyzing Torriani’s education and the context of the mathematical professions during the sixteenth century.